2011
DOI: 10.1021/jp205334v
|View full text |Cite
|
Sign up to set email alerts
|

Facile Microwave Process in Water for the Fabrication of Magnetic Nanorods

Abstract: 1 - ArticleMagnetic nanorods were successfully prepared in water by a simple and fast method through microwave (MW) assisted reduction using akaganeite beta-FeOOH nanorods and hydrazine as precursors and reductor, respectively. Elongated paramagnetic akaganeite precursors are synthesized for the first time using dopamine as green chemical shape-control agent. The nature and the growth mechanism are identified by XRD, Raman spectroscopy and HRTEM analysis. Fast MW reduction process induces a structural and magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 49 publications
4
50
0
Order By: Relevance
“…16 The assynthesized akaganeite nanorods were further coated with a 5-nm-thick silica shell. In brief, 20 mL of the suspension containing as-synthesized akaganeite nanorods (159 mM, Fe ions) were transferred into 50 mL of ethanol solution containing 0.8 mL of aqueous ammonia (25 %) and 150 mg of polyvinylpyrrolidone (PVP).…”
Section: Preparation Of Silica Coated Akaganeite Nanorods (Sio 2 @β-Fmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The assynthesized akaganeite nanorods were further coated with a 5-nm-thick silica shell. In brief, 20 mL of the suspension containing as-synthesized akaganeite nanorods (159 mM, Fe ions) were transferred into 50 mL of ethanol solution containing 0.8 mL of aqueous ammonia (25 %) and 150 mg of polyvinylpyrrolidone (PVP).…”
Section: Preparation Of Silica Coated Akaganeite Nanorods (Sio 2 @β-Fmentioning
confidence: 99%
“…[22][23][24][25][26][27] Moreover, the β-FeOOH phase is important and widely used as a precursor in the 4 preparation of iron, hematite, maghemite and magnetite nanosized materials. 16,[28][29][30][31][32] Akaganeite is an antiferromagnetic material with a Néel temperature in the range of T N ≈ 240-299 K. 12,20,33 A substantial reduction of the Néel temperature, down to T N = 15 K, has been observed in amorphous β-FeOOH nanowires. 19 It has also been observed that the Curie-Weiss temperature varies within a wide range for differently synthesized β-FeOOH materials.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, iron oxide nanoparticles are highly inspiring nanoparticles from an essential research point of view, considering the dependence of the magnetic properties with shape, size, composition, surface and interaction. The iron nanoparticles have several potential applications in medical diagnosis and therapy [1], drug delivery [2], magnetic resonance imaging [3] and cancer hyperthermia treatment [4]. However, the synthesis of iron nanoparticles has been synthesized by various approaches such as hydrothermal [5], sonochemical [6], micro emulsion [7], electrochemical [8], co-precipitation [9], ammonia solutions [10], sol-gel [11], surfactants [12], solvothermal [13], solvents [14], mechano-chemical [15] and emulsion techniques [16].…”
Section: Introductionmentioning
confidence: 99%
“…Motte and co-workers synthesized magnetic nanorods by a two-step one-pot procedure involving the microwave reduction of precursor nanorods obtained in the first step. 25 In this case, the shape control is achieved during the synthesis of the precursor (akaganeite β-FeOOH) using dopamine, which is known for its strong affinity for Fe(III). In the absence of dopamine ligands, mainly hexagonal nanoparticles were obtained, while its presence promoted the growth of rodshaped nanoparticles whose aspect ratio was inversely proportional to the reaction times, decreasing from 5.8 after 2 h reaction time to 4.6 after 4 h. Dopamine plays here a similar role to that of phosphate ions in the above-discussed examples, 23,24 favouring the growth of rod-like structures along the c-axis of the β-FeOOH crystal.…”
Section: Direct Synthesismentioning
confidence: 99%